Effect of low level laser therapy on orthodontic tooth movement: a review article. - Soghra Yassaei; Reza Fekrazad; Neda Shahraki (Tehran University of Medical Sciences, 2013)
Increased duration of fixed orthodontic treatments leads to increased tooth root degeneration, gum inflammation and tooth caries. To decrease the time period of orthodontic treatment, it is essential to facilitate tooth movement or in other words increase the speed of bone remodeling. Use of low level laser therapy is a method for achieving this goal.